THE CORRELATION BETWEEN STUDENTS LEARNING MOTIVATION, STUDENTS LEARNING STYLE AND PEERS WITH MATHEMATICS LEARNING OUTCOMES IN 8TH GRADE STUDENTS IN THE SMP NEGERI 2 BERBAH SLEMAN REGENCY - Liya Gustina; Widayati Widayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Dealing with the low learning motivation, the students who don’t have a good process of learning and peers that don’t support the learning activity are estimated relates to mathematics learning outcomes. This research is aimed to know ‘is there any positive and significant correlation between students learning motivation, students learning style and peers with mathematics learning outcomes in 8th-grade students in odd semester in SMP Negeri Berbah, Sleman Regency in academic year of 2016/2017. The population in this research is all students in class 8 which are spread in 4 classes, in odd semesters of SMP Negeri 2 Berbah Sleman Regency in the academic year of 2016/2017. Then, the sample of this research is taken from 8D class and 8A is as the tested class by using the Random Sampling technique. Data collecting techniques are test and nontest technique. Data collecting instruments are questionnaires. Instruments tested which used are validity test, difference test, and reliability test. The prerequisite test which is used is a normality test, linearity test, and independent test. Data analysis which is used to test the hypothesis is correlation analysis and linear regression analysis. The research result shows that there is a positive and significant correlation between students learning motivation, students learning style, and peers with mathematics learning outcomes, double correlation coefficient (  0,5562 with the regression equality , at 5 % of the significance level, is got  is  and  is , so . It is got that relative contribution of students learning motivation is 21,3092 %, relative contribution of students learning style is 71,4523 % and relative contribution of peers is 7,2385 % then, the effective contribution of the way of students learning is 6,5920%, effective contribution of students learning style is 22, 1038% and effective contribution of peers is 2,2392 %.